Pre-service Teachers Curriculum in Special Education - José Luis Gallego Ortega; Antonio Rodríguez Fuentes (Universidad Autónoma de Madrid, 2018)
This article is mainly concerned with the training of future teachers and more specifically with one of its essential components: pre-service teacher in special education. Our interest is focussed on the knowledges that the future teachers must acquire, as well as on the way of making their didactic actions in order to improve the complete development of their students. This article, after reflecting on the new requests in the pre-service teacher, shows some dilemmas about teachers in Special Education which are analyzed form a theoretical and practical approach (categoric vs. generic training, general vs. specific training), and it is explained a complete proposal derived from the theoretical framework of inclusive education: both ordinary and special teachers with their different roles must collaborate, so their education must be similar and diverse.